Genetic diversity and haplotypes of paediatric hydatid cyst isolates and first occurrence of E. canadensis (G6/G7) in paediatric cases in Turkey - Bakal, Unal; Celik, Figen; Simsek, Sami; Kesik, Harun Kaya; Gunyakti Kilinc, Seyma (Cambridge Univ Press, 2021)
Cystic echinococcosis (CE) is a neglected zoonotic tropical disease caused by Echinococcus granulosus sensu lato. The aim of this study was to investigate the genetic variation of hydatid cyst isolates obtained from surgically confirmed paediatric cases originating from two different regions in eastern Turkey. Seventeen paediatric cases aged between 6 and 16 were operated by open surgery, and the germinal layers of their cysts were obtained for further molecular analyses. After genomic DNA isolation, 875 bp mt-CO1 gene fragments were amplified in all samples by PCR. Then, the unidirectional sequence analyses of the PCR products were carried out. According to the BLAST analyses of 17 sequences, 16 of these sequences were matched with E. granulosus sensu stricto, while one sequence was identified as E. canadensis (G6/G7) for the first time in paediatric cases in Turkey. High haplotype diversity and low nucleotide diversity were observed in the E. granulosus s.s. sequences.
Keywords: Echinococcus granulosus sensu stricto; haplotype analysis; paediatric hydatid cyst